FEM numerical analysis of excimer laser induced modification in alternating multi-layers of amorphous and nano-crystalline silicon films - Conde, J. C. (2012)
UV excimer laser annealing (UV-ELA) is an alternative annealing process that, during the last few years, has gained enormous importance for the CMOS nano-electronic technologies, with the ability to provide films and alloys with electrical and optical properties to fit the desired device performance. The UV-ELA of amorphous (a-) and/or doped nano-crystalline (nc-) silicon films is based on the rapid (nanoseconds) formation of temperature profiles caused by laser radiation that is absorbed in the material and lead to crystallisation, diffusion in solid or even in liquid phase. To achieve the desired temperature profiles and to optimize the parameters involved in the processing of hydrogenated nanocrystalline silicon (nc-Si:H) films with the UV-ELA, a numerical analysis by finite element method (FEM) of a multilayer structure has been performed. The multilayer structures, consisting of thin alternating a-Si:H(10 nm) and n-doped nc-Si:H(60 nm) layers, deposited on a glass substrate, has also been experimentally analyzed. Temperature profiles caused by 193 nm radiation with 25 ns pulse length and energy densities ranging from 50 mJ/cm2 to 400 mJ/cm2 have been calculated. Numerical results allowed us to estimate the dehydrogenation process of the different layers and the diffusion of phosphorous (P) in Si layers as well as their structural modifications as a function of the applied laser energy density. Numerical results are compared with exhaustive characterization of the experimental results.